SCFA production through acidogenic fermentation of industrial waste - Campos, Joana Coutinho (2018)
Polyhydroxyalkanoates (PHA) production from industrial wastes and open mixed cultures (OMC) is a way to reduce process costs. OMC produce PHA from short-chain fatty acids (SCFA), which composition determines the final composition of the polymer and consequently its characteristics. So it is important to understand which operational conditions influence SCFA production during acidogenic fermentation of industrial wastes such as hardwood sulphite spent liquor (HSSL) and cheese whey. This work began with the evaluation of the acidogenic fermentation capacity of HSSL in a continuously stirred tank reactor (CSTR), with emphasis on the influence of the organic loading rate (OLR) and temperature on the process. In the end of the fermentation it was possible to produce a stream with acetic, lactic, propionic and butyric acids and ethanol. The profile of SCFA changed with the OLR, with hydraulic retention time (HRT) and with the age of the culture. A PHA accumulation test was performed with the effluent of the end of the fermentation. With this batch experiment was possible to achieve 32% PHA on dry cell weight, with a 75:25 proportion on 3-hydroxybutyrate and 3-hydroxyvalerate, respectively. In the second part of this work, the acidogenic fermentation of cheese whey in a moving-bed biofilm reactor (MBBR) was studied in order to explore the process in a reactor for biomass retention. The influence of the available surface area, associated with biomass concentration, was studied. The carriers with the largest surface area allowed more biomass growth and consequently more SCFA production. However, an increase in the number of carriers in the reactor does not translate into higher yields possibly due to various limitations of the system. A model based on Michaelis-Menten equation was conceived to evaluate other MBBR designs for fermentation of cheese whey. These results demonstrate the potential of reactors for biomass retention for the acidogenesis of industrial residues.